CRITERIA FOR DELIMITATION OF AGGLOMERATIONS: INTERNATIONAL EXPERIENCE AND NATIONAL PRACTICE (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the current context of globalization, the increasing concentration of population in large cities, and the widespread adoption of urban lifestyles, the issue of agglomeration delimitation has become particularly relevant. Scientifically grounded identification of agglomeration boundaries serves as a foundation for effective territorial development management, resource allocation, and the formulation of socio-economic growth strategies. In Ukraine, it also plays a crucial role as a driver of post-war recovery.At the same time, global practice demonstrates significant variability in the criteria used for agglomeration delimitation, influenced by the peculiarities of administrative-territorial structures, economic interconnections, and demographic dynamics.The study of international experience allows for the identification of methodological approaches proposed by foreign scholars and applied in various countries to define agglomeration boundaries. Meanwhile, Ukraine’s approach to agglomeration formation, which remains in the stage of institutional development, reflects a strong inclination toward adopting international standards while considering national specificities.This article analyzes the key approaches and criteria for agglomeration delimitation, highlights the specificities of their application, and identifies the challenges associated with developing scientifically grounded methodologies for delineating agglomeration boundaries.The purpose of the article is to summarize and analyze approaches to the delimitation of agglomerations in domestic and international academic literature, as well as to identify the specific features of their application in European countries and Ukraine.Research Methods: structural and logical generalization method, comparative analysis, content analysis of scientific publications, systematization and generalization of scientific sources, dialectical approach.The research is based on a comprehensive review of both domestic and international scientific literature, encompassing an in-depth analysis of publications and foundational works addressing the issue of agglomeration delimitation. To further explore the methodological approaches developed by leading scholars and researchers for delineating agglomeration boundaries, content analysis was employed. This facilitated the identification of key conceptual orientations, methodological particularities, and analytical tools shaping the contemporary discourse in this domain.The study highlights the fundamental principles of agglomeration delimitation, including administrative-legal compliance, geographical continuity, functional interaction, and transport accessibility. The findings substantiate the feasibility of conducting agglomeration delimitation based on a spatial-functional approach.
Keywords: delimitation, agglomeration, administrative-territorial unit, territorial communities, post-war recovery, regional economy.